Marketing Endorsement Activities on the Level of Sales and the Existence of Online Shop Tokikubytata - ., Claresta; Johana, Kornelia; ., Soemiadeny (KnE Social Sciences, 2023)
Nowadays, social media is quite famous for promotional media. Social media is now a business land for someone to promote and sell products, goods or services to social media users known as an online shop. The use of endorsements is one of the creative strategies in advertising that online shop sellers often use to introduce and disseminate product information that is owned widely and quickly. This research will focus on the influence of using endorsements on the sale of online shop businesses. This study examines the usefulness of endorsements to increase online shop sales for Tokikubytata. The research method used is descriptive with a qualitative data approach obtained from consumers and online shop owners through written interviews with questionnaires. The research process has several stages, starting from reading books about marketing endorsements, literature and research supporting references, understanding research backgrounds, collecting data, conducting a series of qualitative data analysis processes, and conducting written interviews and field observations. The result of this study show that endorsement is very influential in increasing the number of followers and buyers for Tokikubytata. Endorsement will help in increasing consumer confidence in the products marketed by Tokikubytata. Phenomenological studies in this study are a method used to explore that the phenomenon of endorsement can increase the number of followers for online shop. Keywords: endorsement, Tokikubytata, online shop